Access and Utilization of Online Learning Resources Among Undergraduate Students - Soetan Aderonke Kofo; Onojah Amos Ochayi; Balogun Abdulrasaq Jimoh (Indonesian Journal Of Educational Research and Review, 2022)
Online learning resources have made a significant contribution to teaching and learning. It has been felt that many students are underutilizing online learning resources for various reasons. This study aimed to analyze the online learning resources available to undergraduate students, the level of use of online learning resources by undergraduate students, and examine the challenges faced when accessing and using online learning resources. This research is descriptive research with the type of survey research. 200 students were selected as the sample. Three questions were asked and answered. The research findings revealed that the respondents had heard of web tools for teaching and were familiar with web tools for learning. The institution provided free tablets and internet for students as well. There were enough computers in the school's electronic library with free internet. There were internet cafes in the school environment as well as Students used Smartphones to access and use online learning resources. The study results concluded that online learning resources encourage students in the academic field and assist students in future learning. Based on and conclusions, it is recommended that; Universities must support the distribution of mobile learning devices, the government must provide funds for the provision of bandwidth and e-libraries, and teachers must be involved in the use of online learning resources because this will facilitate the teaching process and encourage students.